In a new york minute ebook - Spencer, Kate (2022)
“A sparkling delight about found and chosen family, being brave even in the tiny moments, and the rewards we can reap when we put our authentic selves out there. What a sweet, hilarious treat.” —Christina Lauren,  New York Times  bestselling author   Franny Doyle is having the worst day. She’s been laid off from her (admittedly mediocre) job, the subway doors ripped her favorite silk dress to ruins, and now she’s flashed her unmentionables to half of lower Manhattan. On the plus side, a dashing stranger came to her rescue with his (Gucci!) suit jacket. On the not-so-plus side, he can’t get away from her fast enough. Worse yet? Someone posted their (entirely not) meet-cute online. Suddenly Franny and her knight-in-couture, Hayes Montgomery III, are the newest social media sensation, and all of New York is shipping #SubwayQTs. Only Franny and Hayes couldn’t be a more disastrous match. She’s fanciful, talkative, and creative. He’s serious, shy, and all about numbers. Luckily, in a city of eight million people, they never have to meet again. Yet somehow, Hayes and Franny keep running into each other—and much to their surprise, they enjoy each other’s company. A lot. But when Franny’s whole world is turned upside down (again!), can she find the courage to trust in herself and finally have the life—and love—she’s always wanted?   A clever, tender rom-com romp for readers of Jasmine Guillory, Abby Jimenez, and Sophie Cousens.   Read this if you love: Opposites attract romance A love letter to New York City An adorable meet disaster Found family